2017
DOI: 10.1038/cr.2017.126
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting promotes adipose thermogenesis and metabolic homeostasis via VEGF-mediated alternative activation of macrophage

Abstract: Intermittent fasting (IF), a periodic energy restriction, has been shown to provide health benefits equivalent to prolonged fasting or caloric restriction. However, our understanding of the underlying mechanisms of IF-mediated metabolic benefits is limited. Here we show that isocaloric IF improves metabolic homeostasis against diet-induced obesity and metabolic dysfunction primarily through adipose thermogenesis in mice. IF-induced metabolic benefits require fasting-mediated increases of vascular endothelial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
147
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(165 citation statements)
references
References 71 publications
11
147
7
Order By: Relevance
“…Two common dieting schemes using in rodent studies include mechanisms, such as increased browning in iWAT, increased thermogenesis, increased vascularization, and switching from M1 to M2 macrophage activation in adipose tissue. 36,37 Moreover, multiple clinical and animal studies, including the present study ( Figures 1G and 2D), indicated that healthy and unhealthy diet switch induced weight cycling ultimately increases body fat gain, specifically in the visceral adipose tissue. 4,38 Notably, the present study demonstrated increased A, qPCR results of Il-6 and Il-8 in primary hepatocytes stimulated with media from indicated 3T3-L1 cells.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Two common dieting schemes using in rodent studies include mechanisms, such as increased browning in iWAT, increased thermogenesis, increased vascularization, and switching from M1 to M2 macrophage activation in adipose tissue. 36,37 Moreover, multiple clinical and animal studies, including the present study ( Figures 1G and 2D), indicated that healthy and unhealthy diet switch induced weight cycling ultimately increases body fat gain, specifically in the visceral adipose tissue. 4,38 Notably, the present study demonstrated increased A, qPCR results of Il-6 and Il-8 in primary hepatocytes stimulated with media from indicated 3T3-L1 cells.…”
Section: Discussionsupporting
confidence: 57%
“…Second, switching between normal chow (NC) or HF and fasting is seen in intermittent fasting study, whereas NC and HF switching is used in weight cycling study with continual access to food as is commonly seen in human society, therefore, some beneficial effects of intermittent fasting may due to a reduction in total caloric intake. However, some intermittent fasting studies with matched total caloric intake also suggest that beneficial effects may due to the physiological changes during fasting, such as fasting-induced increase of VEGF dependent activation of M2 macrophage in white adipose tissue, 37 fasting-induced modifying of gut microbiota 36 or improving of overt circadian rhythms, 39 and fasting-mimicking diet induced pancreatic β-cell regeneration. 40 Weight cycling has also been reported to be accompanied by fluctuations in biochemical parameters, such as blood glucose and blood pressure, indicators of disrupted metabolic homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of high-throughput omics facilitated the elucidation of some of the cellular and molecular mechanisms underlying the beneficial effects of fasting. Nonetheless, the majority of these studies focused on single organ response (i.e., the liver) and, less often, involved two or three organs [10][11][12][13][14][15][16]. The adaptation to energy deprivation, however, requires a multi-organ integration of metabolic modulations to protect the organism from an irreversible loss of resources [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still unclear, how activation of VEGFR2 in WAT could be achieved for the development of effective and safe treatment for humans. Kim et al [1] demonstrate that by allowing mice to fast every three days, VEGF levels were significantly increased in WAT. This was associated with angiogenesis, macrophage polarization towards antiinflammatory M2 type, and beiging of the WAT.…”
Section: Intermittent Fasting (If) Has Beenmentioning
confidence: 99%
“…Rather than storing energy, these cells then start to use extra energy for heat production, which could be a promising therapeutic approach to treat obesity-related metabolic disorders. In a study recently published by Cell Research, Kim et al [1] demonstrate that IF increases vascular endothelial growth factor (VEGF) levels in WAT, which induced angiogenesis, adipose tissue macrophage polarization and WAT browning/beiging. This led to improved insulin sensitivity, which counteracted obesity, and alleviated metabolic syndrome in the mice.…”
Section: Intermittent Fasting (If) Has Beenmentioning
confidence: 99%